School-entry requirements for HPV vaccination: part of the patchwork for HPV-related cancer prevention - Erika L. Thompson; Ellen M. Daley; Tricia Washburn; Kim Salisbury-Keith; Debbie Saslow; Holly B. Fontenot; Gregory D. Zimet (Taylor & Francis Group, 2021)
Human papillomavirus (HPV) vaccination can prevent six types of HPV-related cancers, and approximately, 54.2% of adolescents are up-to-date with the HPV vaccine in the United States. While moderate success has been achieved with provider- and parent-focused interventions, HPV vaccination in the U.S. lags well behind desired goals. In order to maximize HPV vaccination and prevention of HPV-related cancers, it may be prudent to consider state policy approaches, such as school-entry requirements as part of the patchwork of provider, parent, and structural interventions. In this paper, we reviewed the history of efforts to implement school-entry requirements for HPV vaccine, the challenges and benefits associated with implementing these requirements, and the evidence for the effectiveness of school-entry requirements. In addition, we presented new data from Rhode Island's Immunization Information System (IIS) showing how their school-entry requirement, implemented in 2015, has impacted HPV vaccination rates. These registry data indicate that HPV vaccination rates improved significantly after the 2014-2015 school year and policy implementation, and add to the ongoing evidence supporting the value of school-entry requirements for HPV vaccination. School-entry requirements should be considered alongside other initiatives and policies for promoting HPV vaccine uptake. Taking a comprehensive systems approach to HPV vaccination is needed.